Supporting Youth at Risk : A Policy Toolkit for Middle Income Countries - Cunningham, Wendy; Cohan, Lorena M.; Naudeau, Sophie; McGinnis, Linda (World Bank, Washington, DC, 2016)
The World Bank has produced this policy Toolkit in response to a growing demand from our government clients and partners for advice on how to create and implement effective policies for at-risk youth. The author has highlighted 22 policies (six core policies, nine promising policies, and seven general policies) that have been effective in addressing the following five key risk areas for young people around the world: (i) youth unemployment, underemployment, and lack of formal sector employment; (ii) early school leaving; (iii) risky sexual behavior leading to early childbearing and HIV/AIDS; (iv) crime and violence; and (v) substance abuse. The objective of this Toolkit is to serve as a practical guide for policy makers in middle-income countries as well as professionals working within the area of youth development on how to develop and implement an effective policy portfolio to foster healthy and positive youth development.